Analisis Faktor-Faktor yang Berhubungan dengan Kejadian Preeklampsia : Literature Review - Regita Sulistiya Nindya Wijaya; Mika Mediawati; Ririn Indriani (Malang Journal of Midwifery (MAJORY), 2022)
The mortality of maternal is very high in Indoneai. Data shows that as many as 4,627 maternal deaths in Indonesia in 2020, 1,110 cases were caused by pre-eclampsia. Early detection and management of mothers who have a risk of preeclampsia is very important to reduce the risk of maternal death. Therefore, the researchers analyzed the factors associated with the incidence of pre-eclampsia. This study aims to find out the similarities and differences in research journals regarding factors associated with the incidence of pre-eclampsia. The study used literature review with a Systematic Mapping Study design. Data is collected through articles with at least the last 5 years of publication. Ten articles of data sources were obtained from the databases of Google Schoolar, Pubmed, and Garuda. The articles were collected using PEOS, adjusted to the inclusion criteria and then analyzed using the instrument of presenting the results of the literature study. The review technique uses Compare and Contrast by finding similarities and differences from the articles that have been found, so that researchers are able to draw conclusions according to the specific objectives of the researcher. The result was incidence of pre-eclampsia in the article is in the range of 42-323 cases. There are 19 factors associated with the incidence of pre-eclampsia. All factors have p<0.05. Thus, the incidence of pre-eclampsia nationally and internationally is still high. The highest factors causing pre-eclampsia are maternal age and chronicity